Appearances Can Be Deceiving: What Is the Diagnosis for this Community-Acquired Pneumonia? - Frank YH Lin; Coleman Rotstein (Canadian Journal of Infectious Diseases)
A and asbestos exposure (in the 1970s) presented to the emergency department with a one-month history of progressive dyspnea, right-sided pleuritic chest pain, cough productive of white-coloured sputum and malaise. His health problems had commenced four months before presentation while he was vacationing at a northern Ontario resort. At that time, he had felt unwell and had developed a fever with rightsided pleuritic chest pain that radiated to his right shoulder. The diagnosis was an upper respiratory tract infection, made by the local physician; the patient was treated with a 10-day course of cephalexin. Although his condition had initially improved after the antibiotic therapy, during the month before presentation he had experienced increasing fatigue, cough with clear sputum production and a loss of appetite. He also developed worsening right-sided pleuritic chest pain that radiated to the right shoulder, dyspnea and orthopnea. He had no nausea, vomiting, diarrhea or hemoptysis. However, he had lost 4 kg and had drenching night sweats over the previous three and a half months. Further history revealed that he had drunk well water during his vacation in northern Ontario and that several families who were with him at that time also became ill, although he was not aware of the nature of their symptoms.